2014
DOI: 10.4049/jimmunol.1302417
|View full text |Cite
|
Sign up to set email alerts
|

C5a and Bradykinin Receptor Cross-Talk Regulates Innate and Adaptive Immunity in Trypanosoma cruzi Infection

Abstract: Complement and the kallikrein–kinin cascade system are both activated in injured tissues. Little is known about their partnership in the immunopathogenesis of Chagas disease, the chronic infection caused by the intracellular protozoan Trypanosoma cruzi. In this study, we show that pharmacological targeting of the C5a receptor (C5aR) or the bradykinin B2 receptor (B2R) inhibited plasma leakage in hamster cheek pouch topically exposed to tissue culture trypomastigotes (TCTs). Further, angiotensin-converting enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 81 publications
0
30
0
1
Order By: Relevance
“…The anaphylatoxins C3a and C5a are key effector molecules of the complement system that could play an important role in sensing and removal of pathogens and danger 8 . Recently, it has been shown that C3a and C5a can modulate adaptive immunity via interactions with their respective receptors on both innate and adaptive immune cells 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The anaphylatoxins C3a and C5a are key effector molecules of the complement system that could play an important role in sensing and removal of pathogens and danger 8 . Recently, it has been shown that C3a and C5a can modulate adaptive immunity via interactions with their respective receptors on both innate and adaptive immune cells 9, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to FcγRs, anaphylatoxins regulate macrophage and DC function through their impact on TLR signaling. In monocytes/macrophages, C3a and C5a either enhanced TLR‐mediated IL‐6 or IL‐1β production or suppressed it as in case of IL‐12 family cytokines . TLR2 stimulation of DCs in the absence of C5aR1 induced a tolerogenic phenotype with high TGF‐ß production enabling such DCs to promote Treg cell differentiation .…”
Section: Regulation Of C3ar and C5ar1 Signaling By Adaptive Immune Mementioning
confidence: 99%
“…A further potential mechanism for the pleiotropic effects of ACEI is that ACEI (but not AT‐1 blockers) regulate bradykinin BR2 receptor signalling which has effects on innate and adaptive immunity and renal tubular salt handling …”
Section: Mechanism Of Actionmentioning
confidence: 99%